GP217 Markers of endothelial dysfunction sVCAM-1, VEGF and metabolic status in obese adolescents. (June 2019) - novikova, valeria; Gurova, Margarita; Gurina, Olga; Varlamova, Olga; Blinov, Aleksey; Burnysheva, Irina
Abstract : Introduction: Obesity in adolescents is associated with the development of metabolic disorders, chronic inflammation and endothelial dysfunction. Objectives: To determine the peculiarities of metabolic status and presence of markers of endothelial cell dysfunction sVCAM-1 and VEGF-A in adolescents with obesity. Methods: We examined 44 young people: 22 teenagers with obesity (body mass index - BMI – from 30.1 to 42.87) and 22 teenagers with normal physical development (BMI from 18.5 to 24.99). The age of patients ranged from 13 to 18 years (average of 14.25 ±1.2). The following laboratory data was screened: level of glucose, insulin, liver enzymes, lipid profile, uric acid, C reactive protein (CRP). Insulin resistance (IR) was estimated by calculation HOMA-IR index. In addition, we analyzed serum concentrations of vascular cell adhesion molecule 1 (sVCAM-1) and vascular endothelial growth factor A VEGF-A – markers that indicate the presence of endothelial dysfunction. Data was analyzed with the use of statistical package Statistica 10.0 for Windows-10. The significance of the differences was determined at P value <0.05. Results: We have identified the following features of carbohydrates and lipid metabolism in obese adolescents: hyperinsulinemia in 81.8%, insulinresistancy according to results of HOMA-index – in 72.7%, increasing triglycerides level – in 40.9%, decreasing level of LPHD – in 77.3%, increasing level of LPLD in 45.6%. CRP was moderately elevated in 31.8%. Liver enzymes (ALT) were increased by 2–3 times in 40.9% obese children. Concentration of sVCAM-1 (1395.23±264.73 ng/ml vs 847.44±190.23 ng/ml; p< 0.0001) and VEGF-A (75.89±54.79 pg/ml vs 6.22±5.74 pg/ml; p< 0.0001) was higher in patients with obesity compare to the adolescents with the normal BMI. Conclusions: Obesity in adolescents characterized by significant metabolic disturbances with the development of insulin resistance in 81.8%, atherogenic dyslipidemia in 41%, low-grade inflammation in 31.8%, elevation of liver enzymes in 40.9% and increased level of endothelial dysfunction markers (sVCAM-1 level in obese teenagers exceeds level of teenagers with normal BMI more than 2 times, VEGF-A – more than 12 times).